Influencia de la modalidad virtual en los medios de comunicación del cantón Quevedo, durante la pandemia 2020-2021 - Carrasco Macías, Delia (2021)
This research was carried out in the city of Quevedo with the aim of determining the influence of the virtual modality in the media of the Quevedo canton, during the pandemic. The media during the pandemic, due to the virus that the world has been subjected to in the last year, has proven to be very important for everyone. Traditional and digital media have played a role in mass communication, with television, radio and digital newspapers being the main sources of information, which has left traditional newspapers in a difficult economic situation because it is normally used on the street. In the first months of containment, they had almost zero sales, which forced them to migrate to digitization, which made them generate a strong increase in sales, in this way they should be able to demonstrate the importance of mediation between the media. communication and society. However, the democracy of information and the ease of sharing your opinion generates an information situation that leads to false news that only serves to confuse the population because they define the behavior of many people. This is a big problem as a member of this society as we are adapting to this new reality. To counteract the spread of this erroneous information, some social networks have been innovated, such as Facebook, so that in this way they regain the reliability that was affected at the beginning of the pandemic and today, but to a lesser extent. level. At this point, no one can ignore that the pandemic does not exclusively comprise a health crisis, but is what the social sciences describe as a “total social fact”, in the sense that it shakes up all social relations, and shocks the population. integrity of actors, institutions and values. This reality of isolation is an exceptional event that has caused the transformation to new models of life, new consumption habits, and specifically, new forms of consumption of the information media, as well as hobbies, entertainment and culture. Thus, communication with the public, with direct users within the sanitary system, schools and other actors, essential during a public health emergency to achieve ownership of anyone, keeping people properly informed so that it does not cause disorder. of an uninformed and incommunicado society.